An Orthogonal Dynamic Covalent Chemistry Tool for Ring‐Opening Polymerization of Cyclic Oligochalcogenides on Detachable Helical Peptide Templates. Issue 33 (4th May 2022) - Laurent, Quentin; Sakai, Naomi; Matile, Stefan
Abstract: A model system is introduced as a general tool to elaborate on orthogonal templation of dynamic covalent ring‐opening polymerization (ODC‐TROP). The tool consists of 310 helical peptides as unprecedented templates and semicarbazones as orthogonal dynamic covalent linkers. With difficult‐to‐control 1, 2‐dithiolanes, ODC‐TROP on the level of short model oligomers occurs with high templation efficiency, increasing and diminishing upon helix stabilization and denaturation, respectively. Further, an anti‐templated conjugate with mispositioned monomers gave reduced templation upon helix twisting. Even with the "unpolymerizable" 1, 2‐diselenolanes, initial studies already afford mild templation efficiency. These proof‐of‐principle results promise that the here introduced tool, recyclable and enabling late‐stage side chain modification, will be useful to realize ODC‐TROP of intractable or unknown cyclic dynamic covalent monomers for dynamer materials as well as cellular uptake and signaling applications. Abstract : Recyclable with orthogonal dynamic covalent semicarbazone chemistry, 310 helical peptide templates are introduced as a general chemistry tool to enable and tame unfavorable ring‐opening polymerizations by dynamic covalent disulfide and diselenide exchange cascades.